POLA RELASI RUMAH TANGGA KOMUNITAS SANTRI PELAKU PERNIKAHAN DINI - Adib, Muhammad; Siti A'isyah (INTAJ : Jurnal Penelitian Ilmiah, 2019)
The focus of this research is about the pattern of relationships that are built in the households resulting from early marriage among the santri community in three villages in Gondanglegi District, Malang Regency, namely Ganjaran, Putukrejo and Sukosari - three villages with the strongest pesantren base in Gondanglegi region. The starting point is the strengthening of the assumption that early marriage is one of the main causes of domestic violence - where women are always victims, divorce and even trafficking in women and children. The study using this phenomenological approach concluded that the pattern of relationships built in the households resulting from early marriage of the santri community does require an adaptation process, from submission to agreement, with the uniqueness of each partner. However, the households they cultivate persist and last normally as households in general. The teachings of religion and the social values ??about household that they hold firm, as part of the typical character of the santri community, are one of the strength factors.